2011
DOI: 10.1167/11.2.10
|View full text |Cite
|
Sign up to set email alerts
|

Motion processing with two eyes in three dimensions

Abstract: The movement of an object toward or away from the head is perhaps the most critical piece of information an organism can extract from its environment. Such 3D motion produces horizontally opposite motions on the two retinae. Little is known about how or where the visual system combines these two retinal motion signals, relative to the wealth of knowledge about the neural hierarchies involved in 2D motion processing and binocular vision. Canonical conceptions of primate visual processing assert that neurons ear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 64 publications
0
30
0
Order By: Relevance
“…Using a set of binocularly paired or unpaired monocular stimuli comprising many small drifting Gabor patches (termed psuedoplaids), 3D motion percepts have been shown to be consistent with comparisons of pattern motion signals arising from monocular intersection-of-constraints operations (Adelson & Movshon 1982). Crucially, however, the monocular component motion integration can be done over areas much larger than V1 receptive fields (Rokers et al 2011), and component adaptation effects occur even when the local monocular motion signals are in noncorresponding retinal locations between adaptation and test (Greer et al 2016). …”
Section: Binocular Cues For the Perception Of 3d Motionmentioning
confidence: 99%
“…Using a set of binocularly paired or unpaired monocular stimuli comprising many small drifting Gabor patches (termed psuedoplaids), 3D motion percepts have been shown to be consistent with comparisons of pattern motion signals arising from monocular intersection-of-constraints operations (Adelson & Movshon 1982). Crucially, however, the monocular component motion integration can be done over areas much larger than V1 receptive fields (Rokers et al 2011), and component adaptation effects occur even when the local monocular motion signals are in noncorresponding retinal locations between adaptation and test (Greer et al 2016). …”
Section: Binocular Cues For the Perception Of 3d Motionmentioning
confidence: 99%
“…Since similar dichoptic stimuli presented to human observers in the same study resulted in the perception of coherent pattern motion despite the occurrence of binocular rivalry, the ability of dichoptic presentation to negate pattern responding in single neurons suggests that pattern sensitivity in some MT cells may operate monocularly. Furthermore, research on motion-indepth perception has provided evidence that 2-D plaid motion is extracted at a monocular locus prior to binocular recombination to form a 3-D percept (Rokers, Cormack, & Huk, 2009;Rokers, Czuba, Cormack, & Huk, 2011). This is supported by Guo, Benson, and Blakemore (2004), who found that a significant minority of V1 neurons responded to pattern rather than component motion.…”
Section: Discussionmentioning
confidence: 93%
“…This is supported by Guo, Benson, and Blakemore (2004), who found that a significant minority of V1 neurons responded to pattern rather than component motion. Although further research is needed to reconcile evidence for early spatial integration with the limited size of receptive fields in V1 (Hubel & Wiesel, 1974;Rokers et al, 2011), the growing research suggesting that global processing is not exclusively binocular may be useful in resolving inconsistencies in the DI literature. Similarly, the divergence of results at the dichoptic level in the current study suggests that the DI is produced by processing at multiple levels of the visual motion hierarchy.…”
Section: Discussionmentioning
confidence: 99%
“…There is evidence that area MT can support comparisons between velocities in left and right images for computation of 3D motion (Rokers et al, 2009, 2011), despite being binocularly driven. In this case, MT appears to be performing visual processing as if it had access to the original unmixed images.…”
Section: Discussionmentioning
confidence: 99%